2013
DOI: 10.1007/s00415-013-6974-3
|View full text |Cite
|
Sign up to set email alerts
|

Grey and white matter abnormalities in temporal lobe epilepsy with and without mesial temporal sclerosis

Abstract: Temporal lobe epilepsy with (TLE-mts) and without (TLE-no) mesial temporal sclerosis display different patterns of cortical neuronal loss, suggesting that the distribution of white matter damage may also differ between the sub-groups. The purpose of this study was to examine patterns of white matter damage in TLE-mts and TLE-no and to determine if identified changes are related to neuronal loss at the presumed seizure focus. The 4 T diffusion tensor imaging (DTI) and T1-weighted data were acquired for 22 TLE-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
78
3
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 30 publications
18
78
3
11
Order By: Relevance
“…Also it is important to note that their non-MTS group included 5/13 patients with bilateral seizure onset, thus lateralizing differences would likely be more difficult to observe than in other studies such as ours, where the non-MTS group contained solely unilateral TLE. Most recently, Scanlon et al (2013) examined FA abnormalities with tract-based spatial statistics and also found decreased FA in the corpus callosum, in addition to decreased FA in the ipsilateral anterior corona radiata. However, diffusivity measures were not compared in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Also it is important to note that their non-MTS group included 5/13 patients with bilateral seizure onset, thus lateralizing differences would likely be more difficult to observe than in other studies such as ours, where the non-MTS group contained solely unilateral TLE. Most recently, Scanlon et al (2013) examined FA abnormalities with tract-based spatial statistics and also found decreased FA in the corpus callosum, in addition to decreased FA in the ipsilateral anterior corona radiata. However, diffusivity measures were not compared in that study.…”
Section: Discussionmentioning
confidence: 99%
“…TBSS can reduce the effects of local misregistrations by projecting all FA voxels onto the nearest location on a "skeleton" approximating WM tract center [9] [12] [13]. So TBSS has become a kind of popular software to study DTI, and has been used in some studies of various diseases, such as stroke [14], Parkinson [15], epilepsy [16], multiple sclerosis [17], traumatic brain injury [18], schizophrenia [19] and so on. Also some studies of cognitive disorders used TBSS, included mild cognitive impairment (MCI) and AD [9] [20].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the volumetric studies there have been numerous reports based on diffusion imaging in adult temporal lobe epilepsy patients in which bilateral WM alterations can usually be detected in the limbic and non-limbic areas with ipsilateral predominance [10][11][12][13][14][15][16]. These changes are more extensive in patients with mesiotemporal sclerosis than in the non-lesional group [11,18]. Although the underlying cause is not clear for such alterations, several possible theories exist.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that structural abnormalities associated with MTLE-HS involve not only the hippocampus and the structures of the limbic system [4][5][6][7], but also the bilateral white matter (WM) with ipsilateral predominance [8][9][10][11][12][13][14][15][16][17]. It might be hypothesized that neuronal dysfunction/loss in the sclerotic hippocampus causes damage to WM structures connected to the epileptic foci due to the excitotoxic effects of the spreading epileptogenic activity which then induces microstructural abnormalities far away from the seizure focus [8,18]. Over the last years, diffusion-weighted imaging (DWI) was established as a useful tool to measure microstructural changes of the brain tissue in a variety of neurological diseases [19,20], including epilepsy [21].…”
Section: Introductionmentioning
confidence: 99%